Inconscio, fantasia, immaginazione: alcune riflessioni sulle parole della teoria della nascita e sulla loro storia - Anzilotti, Carlo; Armando, David (Il sogno della farfalla, 2024)
The aim of this article is to retrace the thread of a line of research, which had begun in the 1990s within the framework of Collective Analysis, about the history of the words with which human mental reality has been defined throughout centuries. The research was initially focused on the term “unconscious”, and subsequently shifted towards the term “fantasy” which had been adopted in 1970 by Fagioli to theorize the dynamic of human birth. In the Renaissance tradition, “fantasy”, together with “imagination”, expressed a dimension which differed from that of reason, a thought linked to the eyes and the gaze, capable of influencing one’s own and others’ mental and bodily reality. These two terms underwent a twist between the 17th and 18th centuries, from which their meaning was depowered and reduced to that of deception and a source of error and madness. The authors trace, according to their distinct historical and psychiatric perspectives, the subsequent developments of the words “fantasy” and “imagination”, and the new meanings they took on in Fagioli’s thought.